Políticas públicas para la economía solidaria en Colombia, antecedentes y perspectivas en el posconflicto (2017)
From an epistemological position in the social sciences and particularly in political science , the next article reflects on public policies that are designed and implemented in Colombia for the solidarity economy . It holds that in the country a restrictive view of the solidarity economy has had profound implications for the development of this sector and policies designed to him institutionalized . Today when Colombian society seeks ways to end an armed conflict that has affected for decades and build a peaceful society , it is necessary to look back on the solidarity and the solidarity economy , which involves reviewing our paradigms . Peace and needs a legal framework that institutional viability , a cultural framework to forgiveness and reconciliation , a financial framework enabling consolidation is also required . Peace requires a more caring economy.